The impact of the limbal niche interactions on the self-renewal capability of limbal epithelial stem cells - Aghazadeh, Sara; Peng, Qiuyue; Dardmeh, Fereshteh; Østergaard Hjortdal, Jesper; Zachar, Vladimir; Alipour, Hiva (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThe corneal homeostasis is maintained by limbal epithelial stem cells (LESCs), which reside in the limbal niche. This microenvironment comprises the cells, the extracellular matrix (ECM), and their interactions that balance the quiescent and proliferative states of LESCs. The stress caused by removing the cells from their niche triggers the quiescent stem cells to enter the proliferative state, which is beneficial for in vitro expansion, but reduces their self-renewal capability, making them less suitable for transplantation. Fibronectin (FN), a key ECM component, widely used in tissue engineering and scaffold structure, has been shown to preserve the self-renewal ability of LESCs in vitro. In parallel, paracrine growth factors are crucial for maintaining limbal niche homeostasis and promoting corneal epithelial regeneration. Limbal-niche-cells-conditioned media is a potential reservoir of limbal niche paracrine growth factors. However, whether utilizing fibronectin and limbal-niche-cells-conditioned media can sustain or enhance the stemness and proliferation ability of LESCs in vitro has not yet been investigated.MethodsPrimary cultures of limbal niche cells, including LESCs, limbal mesenchymal stromal cells (LMSCs), and limbal melanocytes (LM), were established from remnant human corneal transplant specimens, and human epidermal melanocytes (HEMn) were included as a negative control. The proliferation ability (doubling time) and self-renewal potential (as assessed by PEDF and HES1 gene expressions) of LESCs were evaluated after culture in LM-, LMSC-, and HEMn-conditioned media, as well as coating with 3, 5, and 8 µg/cm2 concentrations of FN.ResultsCompared to the control group, the LMSC- and LM-conditioned media showed a clear trend towards upregulated PEDF and HES1 gene expressions. FN coating generally upregulated the expression of PEDF and HES1 genes, with this effect being most prominent at 3 µg/cm2.ConclusionThese findings illustrate the potential of utilizing niche-cell-conditioned media and direct contact with FN on the self-renewal of LESCs in vitro. Further research is required to provide a more comprehensive understanding of these effects and to elucidate the underlying mechanisms of action.